Host switching in a generalist parasitoid: contrasting transient and transgenerational costs associated with novel and original host species. Issue 2 (3rd January 2015) - Jones, Thomas S.; Bilton, Adam R.; Mak, Lorraine; Sait, Steven M.
Abstract Parasitoids face challenges by switching between host species that influence survival and fitness, determine their role in structuring communities, influence species invasions, and affect their importance as biocontrol agents. In the generalist parasitoid, Venturia canescens (Gravenhorst) (Hymenoptera: Ichneumonidae), we investigated the costs in encapsulation, survival, and body size on juveniles when adult parasitoids switched from their original host, Plodia interpunctella (Hübner) (Lepidotera, Pyralidae) to a novel host, Ephestia kuehniella (Zeller) (Lepidoptera, Pyralidae), over multiple generations. Switching had an initial survival cost for juvenile parasitoids in the novel host, but increased survival occurred within two generations. Conversely, mortality in the original host increased. Body size, a proxy for fecundity, also increased with the number of generations in the novel host species, reflecting adaptation or maternal effects due to the larger size of the novel host, and therefore greater resources available to the developing parasitoid. Switching to a novel host appears to have initial costs for a parasitoid, even when the novel host may be better quality, but the costs rapidly diminish. We predict that the net cost of switching to a novel host for parasitoids will be complex and will depend on the initial reduction in fitness from parasitizing a novel host versus local adaptations against parasitoids in the original host.